Regenerating Urban Industrial Waterfront: Synergies Between Resilience and the Active Public Realm - Madasamy,Sumesh Thangam (2025)
Stavanger, long recognized as Norway's "oil capital", stands at a critical turning point as it transitions towards a resilient, post-oil future. This thesis explores how the regeneration of Østre Havn, once a industrial waterfront zone can- strengthen the relationship between the city and its harbour while promoting ecological, social and spatial resilience. Through a design-based research approach combining document analysis, field observation, and spatial synthesis, the study investigates how underused industrial edges can evolve into vibrant, inclusive, and climate adaptive urban districts. The design proposes a layered waterfront strategy integrating adaptive flood edge, mixed-use resilience core, and seasonal cultural activation to promote year-round liveability. Nature-based solutions, active mobility networks and cultural programming are used to reconnect the waterfront to the urban core and enhance everyday public life. Aligned with Stavanger's climate the municipal goals, the project envisions a model for post -industrial transformation, where resilient landscapes and active public realms coexists. Ultimately, the thesis contributes to boarder discussion on sustainable urban regeneration in mid sized Nordic cities navigating post-carbon transitions.
Keywords: Urban waterfront regeneration; Climate-responsive urban design; Resilience and Liveability; Public realm activation; Sustainable Urban Design (LTH)